Evaluation of urban heat islands using local climate zones and the influence of sea-land breeze. (April 2020) - Zhou, Xilin; Okaze, Tsubasa; Ren, Chao; Cai, Meng; Ishida, Yasuyuki; Watanabe, Hironori; Mochida, Akashi
Highlights: The WUDAPT L0 method was used to classify LCZ types in Sendai, a typical Japanese metropolitan city, and the OA of our LCZ classification was 92.59 % using an independent dataset. Both surface and ambient urban heat island analysis based on LCZ classes with GIS-based detected geometric and land cover properties are made. LCZ map was found to be generally consistent with land surface temperature(LST) distribution but not match well with air temperature distribution. By dividing Sendai into two regions along its urban center, the mitigating effects of sea-land breeze on the magnitudes of UHIs in each urban-rural area were demonstrated. This study confirmed that the LCZ scheme can be used by urban planners to assess both surface UHI (SUHI) and UHI effects, and proposed a feasible process for developing targeted UHI mitigation strategies. Abstract: The Local Climate Zone (LCZ) scheme is an urban form and land cover/land use classification system used to study urban heat islands (UHIs). Many studies have evaluated the relationship between LCZs and air temperature. While the intensity and spatial pattern of an UHI can be influenced by the land-sea breeze, especially in coastal cities, few studies have been done to examine this using the LCZ scheme. In this study, Sendai, Japan, has been selected as a case study to evaluate whether the LCZ scheme can be used to study UHIs that are exposed to sea-land breeze since it has two urban-rural areas: mountain side and coastal side. UHI analysis was based on LCZ classes with GIS-derived geometric and land cover properties. By dividing Sendai into two regions along its urban center, the mitigating effects of sea-land breeze on the magnitudes of UHIs in each urban-rural area were demonstrated. Based on the results of this study, two specific UHI mitigation strategies were proposed for Sendai. This study confirmed that the LCZ scheme can be used by urban planners to assess both surface UHI (SUHI) and UHI effects, and proposed a feasible process for developing targeted UHI mitigation strategies.